Mayfly diversity in the brazilian tropical headwaters of Serra do Cipó - Michael Goulart; Marcos Callisto (Brazilian Archives of Biology and Technology, 2005)
The objectives of this study were to evaluate spatial and seasonal distribution, assemblage structure and substrate associations of mayfly nymphs in five lotic ecosystems in the headwaters of the Doce River and São Francisco River watersheds, Brazil. Samples were taken in 24 sampling stations during rainy and dry seasons in 1998. In total, 7,066 organisms were collected, belonging to 27 genera and 6 families of Ephemeroptera. The dominant taxa were Americabaetis, Paracloeodes, Leptohyphes and Hagenulus. During the rainy period, the São Francisco River watershed showed higher taxonomic richness, diversity and evenness, while in the dry period, the taxonomic richness was higher in Doce River watershed. No significant differences were found in the taxonomic richness, diversity, evenness and density of mayfly assemblages between the two studied sampling periods. The results suggested that the diversity of the mayfly assemblages in tropical headwaters of Serra do Cipó would be probably due to ecosystem and watershed characteristics. Os objetivos foram avaliar a distribuição espaço-temporal, estrutura de assembléias e associações de ninfas de Ephemeroptera com substratos em 5 ecossistemas lóticos nas nascentes das bacias dos rios Doce e São Francisco, Brasil. As amostragens foram realizadas em 24 estações, nos períodos de chuvas e seca de 1998. No total, 7,066 organismos foram coletados, pertencentes a 27 gêneros e 6 famílias. Os taxa dominantes foram Americabaetis, Paracloeodes, Leptohyphes e Hagenulus. No período de chuvas foram observados maiores valores dos indices de riqueza taxonômica, diversidade e equitabilidade na bacia do rio São Francisco, enquanto que no período de seca, a riqueza taxonômica foi maior na bacia do rio Doce. Não foram encontradas diferenças significativas dos valores dos indices de riqueza, equitabilidade, diversidade e densidade de ninfas de Ephemeroptera entre os dois períodos estudados. Os resultados obtidos sugerem que a diversidade das assembléias de Ephemeroptera nas cabeceiras da Serra do Cipó são provavelmente devido a características ecológicas dos ecossistemas aquáticos e bacias hidrográficas estudadas.